A Scientometric Visualization Analysis for Natural Products on Cancer Research from 2008 to 2020 - Chen, Haitao; Li, Rongrong; Zhang, Fan; Yao, Qinghua; Guo, Yong (Frontiers in Pharmacology, 2021)
Background: An increasing number of studies have shown that natural products have anti-tumor effects, and it has become a hotspot in cancer research. However, few bibliometric analyses have been examined in this field systematically. The current study aimed to explore the status and provide the developing trends in the natural products on cancer research. Methods: Publications on natural products in cancer research were extracted from the Web of Science core collection database. CiteSpace (5.6.R3) software and GraphPad prism 6 were used to analyze and plot the references. Results: On February 1, 2021, 34611 records of natural products in cancer research published from 2008 to 2020 were collected. The USA was the leading driving force, with a strong academic reputation in this area. The top-contributing institutions was the Chinese Academy of Sciences. Most publications were published in Molecules. Efferth Thomas was the most prolific author, while Newman DJ was the most cited frequently co-cited author. Flavonoid, curcumin, and polyphenol were the most widely studied natural products. Oleanolic acid and rosmarinic acid have gradually become research hotspots recently. Breast cancer, prostate cancer and colorectal cancer were the most common types of cancer in this field. “Natural killer cell” was the leading research hotspot. The keywords of “leaf extract”, “molecular docking” and “gold nanoparticle” appeared most recently as research frontiers. Conclusion: Our results provided a general overview of the major research directions of natural products research in cancer. The mechanisms of natural products, especially those related to molecular docking, gold nanoparticle, gut microbiota, and immune checkpoint may soon become hotspots and should be closely monitored.